A Bibliometric Study Investigating the Emerging Digital Behaviour Trends in Education: Implications for Teaching and Learning Practices - Trihantoyo, Syunu; Achmad Supriyanto; Amrozi Khamidi; Muhammad Faizal Bin A. Ghani; Muhamad Sholeh (Journal of Education Technology, 2024)
Recent studies have indicated a significant increase in the investigation of digital behaviour in education, coinciding with the advent of distance learning in the aftermath of the global pandemic. The objective of this study is to analyse contemporary research trends on digital behaviour in education through bibliometric analysis of data sourced from Scopus. This research method employs a literature review with bibliometric analysis.The research stage was conducted by determining: (i) the purpose and scope of the study, (ii) bibliometric study techniques, (iii) data collection, (iv) data analysis, and (v) reporting findings.Data analysis was carried out by determining keywords in the data collection process, namely "digital behavior" and "education".A total of 66 relevant articles were identified from Scopus data sources between 2011 and 2024. The results of the analysis revealed a significant relationship between digital behaviour research and education, with this trend capturing important momentum starting in 2020. This indicates that the integration of digital behaviour in education during the pandemic has driven a substantial shift in the learning process.The findings recommend the long-term adoption of educational technology in shaping digital behaviour as an integral aspect of the education system. The implications of the research highlight the need for teaching methods and educational policies to maximize the potential of technology in supporting effective and meaningful learning.